Experimental and numerical modeling of bridge piers having a different numbers of axis - Goknur Elif Yarbasi Kayhanlar; Alpaslan Yarar (Romanian Journal of Ecology & Environmental Chemistry, 2023)
The interaction of bridge piers and currents with each other is mutual. As a result of this interaction, it has been determined that one of the main causes of damage to bridges is the scouring of bridge piers. One of the factors on which the scouring procedure depends is the flow velocity. For this reason, in this study, the velocity distributions that occur before the bridge piers, which are positioned as single axis and double axis, were examined physically and numerically. In experimental studies, the reading values obtained by using ADV were compared with the results obtained from the ANSYS-Fluent package program used in numerical modeling. The performance of the model used and the effects of placing the piers as single axis and double axis were evaluated. As a result of the study, it was determined that the ANSYS used in determining the flow velocity area was very compatible with the experimental results and that the flow velocity acting in the system obtained by placing the bridge piers as a single axis is larger.